How Readable Is the Information the United Kingdom's Statutory Health and Social Care Professional Regulators Provide for the Public to Engage With Fitness to Practise Processes? - Sharif Haider; Louise M. Wallace (Wiley, 2024)
ABSTRACT Background The public are an important source of notifications and evidence for the investigation of concerns by regulators of professionals. The website is an important source of information for the public, but the complexity of information presented to engage with the public is unknown. Objectives This study explored the readability of information provided for the public to engage with fitness to practise processes by examining the websites of the 13 UK statutory health and social care professional regulators. Methods Six readability algorithms were utilised to calculate the readability scores of 180 general and 8 easy‐read documents published for the 15 sites of the United Kingdom's 13 health and social care statutory professional regulatory bodies. These tests were the Flesch Kincaid Reading Ease, the Flesch Kincaid Grade Level, the Gunning Fog Score, the Simple Measure of Gobbledygook (SMOG) Index, the Coleman Liau Index and the Automated Readability Index (ARI). Results All the fitness to practise documents analysed in this study are written at a level too difficult for most of the general population to read, except one easy‐read document. There was also considerable variation in readability across resources for the same regulator, which could be confusing. Regulatory bodies risk excluding a large proportion of UK adults who may want to engage with professional regulatory proceedings. Conclusions This is the first comparative analysis of readability conducted independent of the regulators of the fitness to practise website documents of health and social care regulators. The public are a key source of evidence in regulatory proceedings. Regulators could improve public engagement by addressing the complexity of language used. Public Contribution Our advisory group of people with lived experience of involvement as members of the public in fitness to practise proceedings discussed the findings and contributed to the recommendations.